Are 1st‐trimester β‐human chorionic gonadotrophin and pregnancy‐associated plasma protein A levels predictive of intrapartum fetal compromise in a selected normal population?. (29th April 2014) - Prior, Tomas; Mullins, Edward; Bennett, Phillip; Kumar, Sailesh
<x xml:space="preserve">Abstract</x> Background The incidence of cerebral palsy in term infants has not changed over the last 30 years. Current intrapartum monitoring techniques are limited by their inherent poor specificity. Changes in fetal haemodynamics in the term fetus, similar to those seen in fetal growth restriction, have been associated with an increased risk of subsequent intrapartum fetal compromise. Alterations in first‐trimester β‐hCG and PAPP‐A levels are predictive of fetal growth restriction. Aims In this study, we aimed to establish whether first‐trimester β‐hCG and PAPP‐A levels were predictive of fetal compromise in labour and whether these first‐trimester markers could be correlated with fetal haemodynamics at term in a low‐risk population. Materials and Methods Over a two‐year period, 427 women with low risk, uncomplicated pregnancies were recruited to this study. All participants underwent a prelabour ultrasound examination during which fetal biometry and haemodynamics were assessed. First‐trimester β‐hCG and PAPP‐A levels were recorded from the case notes. All cases were followed up within 48 hours of delivery, and first‐trimester β‐hCG and PAPP‐A levels correlated with intrapartum outcomes and fetal haemodynamics. Results No significant relationship between first‐trimester β‐hCG and PAPP‐A levels and subsequent intrapartum fetal compromise was observed. Weak but significant correlations were observed between β‐hCG levels and umbilical venous flow rate, as well as PAPP‐A levels and uterine artery pulsatility index. Conclusions β‐hCG and PAPP‐A levels measured during the first trimester are not predictive of subsequent intrapartum fetal compromise within a low‐risk population.